ANALYSIS OF LIQUIDITY AND SOLVENCY OF ECONOMIC ENTITIES: ESSENCE, SIGNIFICANCE AND IMPACT ON ECONOMIC SECURITY - Schneider, V.V; Zorina, A.A (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2020)
In market conditions, the most important task at the microeconomic level is to assess the liquidity and solvency of economic entities from the perspective of financial stability, business efficiency and economic security. Effective use of the resource potential of economic entities is based on the need to account for financial flows, receivables and property using new methods of analysis, which contribute to the process of business development and ensuring its security. Characteristic trends in the development of world civilization are directly related to the process of harmonization of international accounting and financial legislation aimed at maintaining the development of the economy and the security of participants in economic relations in particular and the state as a whole. The emergence of a real need to improve the accounting and tool base for analyzing the liquidity and solvency of economic entities, the development of adaptive methods for conducting analytical procedures make it possible to assess the level of sustainable development and security of economic entities. In this regard, the dominant role is played by accounting and analytical support for assessing the liquidity and solvency of an economic entity based on the study of cash flows. Currently, traditional methods of analyzing indicators that determine the effectiveness of economic entities are used, calculated on the basis of financial statements and used in the process of analytical research and forecasting. Indicators that characterize the level of liquidity and solvency are indicators of the initial assessment of the level of financial stability. Of the main analytical methods, select the method based on the estimated future cash flows and use of accounting engineering tools with the aim of providing objective and accessible information on the financial status of an economic entity to determine the cost of the business, which guide stakeholder decisions.